Subdural Hemorrhage after Scoliosis and Detethering of Cord Surgery - Rohan Bhimani; Fardeen Bhimani; Preeti Singh (Case Reports in Medicine)
Introduction. Intracranial hypotension may occur when CSF leaks from the subarachnoid space. Formation of intracranial, subdural, and subarachnoid hemorrhage has been observed after significant CSF leak as seen in lumbar puncture or ventricular shunt placement. However, very few cases, referring to these remote complications following spine surgery, have been described in literature. We present a case of a 10-year-old male child operated for idiopathic scoliosis with low-lying conus medullaris who postoperatively developed subdural hemorrhage. Case Report. A case of a 10-year-old male operated for idiopathic scoliosis with low-lying conus medullaris is presented. To correct this, detethering was done at the L3 level, laminectomy was done from L2 to L3 with pedicular screw fixation from T3 to L2, and bone grafting with right costoplasty was done from the 3rd to the 6th ribs. On the 5th day postoperatively, the patient developed convulsions and drowsiness and recovered subsequently by postoperative day 7. Conclusion. We report a rare case of an acute intracranial subdural hemorrhage caused by intracranial hypotension following scoliosis and detethering of cord surgery. This report highlights the potential morbidity associated with CSF leak occurring after this surgery.